Additively manufactured geopolymer structured heterogeneous catalysts for biodiesel production. (June 2021) - Botti, R.F.; Innocentini, M.D.M.; Faleiros, T.A.; Mello, M.F.; Flumignan, D.L.; Santos, L.K.; Franchin, G.; Colombo, P.
Highlights: Geopolymer lattices with tailored hierarchical porosity produced via direct writing. Enhanced 3D lattice catalyst for continuous production of biodiesel. Biodiesel yield up to 85%. No need for secondary filtration process for products separation. Abstract: The manufacturing of non-stochastic (lattice) scaffolds by Direct Ink Writing is attractive for catalytic fluid flow applications, as it enables the optimization of not only the desired chemically active formulation but also of porosity, pore size, mechanical strength and permeability of the substrate. In this work, three types of geopolymer compositions containing sodium, potassium or a mixture of both were tested for the printing of lattices used as heterogeneous alkaline catalysts in the processing of fatty acid methyl esters (biodiesel). The rheology of the inks was studied and optimized before the printing process. The geometry chosen was a circular lattice with 24 mm diameter and 9.6 mm height, with shifted layers and 840 μm thick struts. The fabricated Na, K and Na+K bodies possessed open porosity values of 58.3 ± 0.02, 63.6 ± 0.02 and 63.5 ± 0.01 vol% and compressive strength of 4.1 ± 1.2, 2.2 ± 0.6 and 2.6 ± 0.4 MPa, respectively. The catalytic activity for the transesterification of soybean oil was assessed and the biodiesel yield was quantified by GC-FID. High FAME contents (73.5, 85.3 and 71.3%) were achieved for the Na, K and Na-K lattices, respectively. Graphical abstract: Image, graphical abstract